Multi-layer structure TiCoNbAl-based composite material brake disc and preparation method thereof
By designing a multi-layer structure TiCoNbAl matrix composite brake disc, the problem of degradation in the performance of existing cast iron brake discs under high temperature conditions is solved, and excellent high temperature resistance, thermal conductivity and friction wear performance are achieved, and braking accuracy and automobile safety are improved.
Patent Information
- Application Number
- CN202411812216.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The existing cast iron brake discs have poor heat dissipation and high temperature resistance under high temperature conditions, resulting in reduced stiffness and wear resistance, short service life, affecting braking accuracy and car safety.
The multi-layer structure TiCoNbAl matrix composite brake disc is adopted, and the material ratio and utilization rate are optimized through the overlapping composition of the friction layer, the thermal conductivity and the matrix layer, and the material ratio and utilization rate are improved, and the heat conduction ability and tribological properties are improved.
It significantly improves the high temperature resistance, thermal conductivity and friction wear performance of the brake disc, extends the service life, and improves braking accuracy and car safety.
Smart Images

Figure CN119703090A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of automobile brake pads, separators, brake discs and other parts, and relates to the technical field of TiCoNbAl-based composite brake discs, and specifically to a multi-layer TiCoNbAl-based composite brake disc and a preparation method thereof. Background Art
[0002] As the automotive industry develops towards safety and comfort, higher and higher requirements are placed on the automotive braking system. The brake disc is a key component in the braking system (Yang Longbao, Performance Analysis of Automotive Disc Brakes Based on ANSYS Workbench [D], Guangxi University, 2013.). The brake disc generates a lot of heat during operation, which causes the temperature of the brake disc friction surface to rise instantly (Liu Yu, Shan Yingchun, Liu Xiandong, He Tian. Effect of High Temperature on Thermal Fatigue Crack Initiation Life of Automotive Gray Cast Iron Brake Discs [J]. Journal of Mechanical Engineering, 2019, 55(08): 97-105.). However, the heat dissipation capacity and high temperature resistance of the commonly used cast iron brake discs are relatively poor. Under high temperature conditions, their stiffness and wear resistance decrease significantly, their service life is short, and their braking accuracy stability and precision are small, which seriously affects the service life, reliability and vehicle safety of the brake disc. Therefore, it is very important to design and develop a new type of brake disc with excellent high temperature resistance, thermal conductivity and excellent tribological properties.
[0003] The patent document with the announcement number CN107100949B discloses a combined composite brake disc and a preparation method and application thereof, wherein the combined composite brake disc comprises a friction disc and a connecting support disc, the friction disc is made of a carbon-ceramic composite material, the gradient aluminum-based composite material contains SiC, the gradient aluminum-based composite material is divided into an E region and an F region according to the SiC content, the SiC content of any part in the E region is greater than the SiC content of any part in the F region, the connecting support disc is made of a gradient aluminum-based composite material compounded by hot pressing, the combined composite brake disc comprises a carbon-ceramic composite friction disc and a gradient aluminum-based composite connecting support disc; the carbon-ceramic composite friction disc and the gradient aluminum-based composite connecting support disc are connected into one by riveting. Compared with the integral steel disc, the combined composite brake disc provided in the patent document has significant weight reduction and high thermal conductivity, and the high heat brought by the friction disc during braking will not cause significant creep of the material, but the friction reduction and anti-wear performance of the combined composite brake disc still needs to be further improved.
[0004] The patent document with the announcement number CN112413012B discloses a composite brake disc, including a base layer that bears loads, a composite layer that provides friction braking force, the base layer and the composite layer are bonded to each other by metallurgical bonding, a transition layer is generated at the interface where the base layer and the composite layer are bonded to each other, and a reinforcement structure connecting the base layer and the composite layer is formed in the transition layer. The composite brake disc provided in the patent document generates a transition layer between the base layer and the composite layer by metallurgical bonding, which improves the bonding force between the base layer and the composite layer to a certain extent, and reduces the risk of failure such as cracking between the composite layer and the base layer during hot and cold fatigue. However, the friction reduction and anti-wear performance of the composite brake disc still needs to be further improved. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a multi-layer TiCoNbAl-based composite brake disc and a preparation method thereof. In order to improve the thermal conductivity, temperature adaptability and tribological properties of the brake disc, the present invention uses TiCoNbAl-based alloy as a matrix material to design and prepare a multi-layer TiCoNbAl-based composite brake disc with excellent high temperature resistance, thermal conductivity and friction and wear reduction performance. The multi-layer composite brake disc not only optimizes the material ratio, but also improves the material utilization rate and reduces the production cost.
[0006] The present invention adopts the following technical solution to solve the above technical problems: a multi-layer TiCoNbAl-based composite brake disc, which is composed of a friction layer, a heat conductive layer and a matrix layer laminated in sequence, wherein the layer thickness ratio of the friction layer, the heat conductive layer and the matrix layer is (12-18): (25-38): (45-65); the mass fractions of the TiCoNbAl-based alloy, the anti-wear agent, the heat conductive agent, the reinforcing agent and the curing agent in the friction layer are (8-10) wt.%, (30-40) wt.%, (10-12) wt.%, (13-25) respectively. wt.% and (15-35)wt.%; the mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the thermal conductive layer are (25-35)wt.%, (12-18)wt.%, (10-18)wt.%, (30-45)wt.% and (5-10)wt.% respectively; the matrix layer is 100wt.% TiCoNbAl-based alloy; the friction coefficient of the multilayer TiCoNbAl-based composite brake disc is moderate and has a small fluctuation range. The friction coefficient is 0.72-1.03 and the wear rate is (2.97-3.85)×10 -6 cm 3 ·N -1 ·m -1 .
[0007] Furthermore, the anti-wear agent in the friction layer is composed of (30-35) wt.% cerium lanthanum rare earth, (25-30) wt.% cubic boron nitride, (20-25) wt.% calcium fluoride and (15-20) wt.% barium fluoride; the heat transfer agent is composed of (30-50) wt.% graphene, (20-30) wt.% silicene and (25-40) wt.% tungsten disulfide; the reinforcing agent is composed of (35-50) wt.% basic The invention is composed of magnesium sulfate whiskers, (20-35) wt.% potassium titanate whiskers and (25-40) wt.% calcium carbonate whiskers; the curing agent is composed of (50-65) wt.% aluminum-based alloy, (10-20) wt.% econazole ointment and (20-35) wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is (45-60) at.% Al-(20-35) at.% Ag-(10-25) at.% Sn.
[0008] Furthermore, the anti-wear agent in the thermal conductive layer is composed of (20-30) wt.% cerium lanthanum rare earth, (30-45) wt.% cubic boron nitride, (20-25) wt.% calcium fluoride and (15-20) wt.% barium fluoride; the thermal conductive agent is composed of (25-45) wt.% graphene, (20-40) wt.% silicene and (30-45) wt.% tungsten disulfide; the reinforcing agent is composed of (35-45) wt.% basic The invention comprises magnesium sulfate whiskers, (20-45) wt.% potassium titanate whiskers and (20-40) wt.% calcium carbonate whiskers; the curing agent comprises (20-45) wt.% aluminum-based alloy, (15-25) wt.% econazole ointment and (40-60) wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is (30-45) at.% Al-(35-50) at.% Ag-(15-30) at.% Sn, Furthermore, the composition ratio of the TiCoNbAl-based alloy in the friction layer, the heat-conducting layer and the matrix layer is (55-67) at.% Ti - (12-14.5) at.% Co - (9-13) at.% Nb - (8-12) at.% Al - (2.9-4) at.% B - (0.5-0.9) at.% Tb - (0.3-0.6) at.% Ce - (0.3-0.5) at.% Yb.
[0009] The preparation method of the multi-layer TiCoNbAl-based composite material brake disc described in the present invention has a specific preparation process: using TiCoNbAl-based alloy, anti-wear agent, heat conductive agent, reinforcing agent and curing agent as raw materials, and sequentially undergoing material design, calculation, formulation, vibration mixing, hot pressing, spark plasma sintering, curing heat treatment and subsequent machining of each layer to obtain a multi-layer TiCoNbAl-based composite material brake disc.
[0010] The method for preparing the multi-layer TiCoNbAl-based composite material brake disc of the present invention comprises the following specific preparation steps: 1) Weigh the raw materials according to the various components of the friction layer, heat conductive layer and matrix layer in the multilayer TiCoNbAl-based composite material; 2) The powders of each layer of materials obtained in step 1) are subjected to mechanical vibration mixing treatment, wherein the mechanical vibration frequency is 65-95 Hz, the vibration force is 9000-11000 N, and the vibration time is 80-90 min; 3) hot pressing and sintering the uniformly mixed powders of each layer obtained in step 2), wherein the pressure applied in the hot pressing is 10-12 MPa, the pressing temperature is 100-135°C, the heat preservation and pressure holding time is 150-165 min, the air is released for 5-6 seconds every 20-25 seconds, and the operation is repeated 6-8 times; 4) The three-layer pressed sheet obtained in step 3) is sequentially loaded into a graphite mold according to the order of the friction layer, the heat conductive layer and the substrate layer for spark plasma sintering, wherein the sintering temperature is 1000-1100° C., the sintering heating rate is 90-110° C. / min, the sintering pressure is 22-25 MPa, the sintering holding time is 125-145 min, the sintering protective gas is argon, and the argon gas introduction rate is 70-105 mL / min; 5) subjecting the brake disc obtained in step 4) to a curing heat treatment process to improve the bonding performance of each layer of powder, wherein the curing heat treatment is first heated to 120-145°C in a vacuum drying oven for 2.5-3.5 hours, then heated to 175-185°C for 6.5-7.5 hours, then heated to 220-250°C for 3.2-3.6 hours, and finally gradually cooled to room temperature; 6) The brake disc obtained in step 5) is subsequently machined, and the brake disc is respectively subjected to disc grinding by a grinding device according to technical requirements, and the burrs and flashes around the brake disc are cleaned by a polishing machine and electrostatic spraying is performed, and finally a multilayer TiCoNbAl-based composite brake disc is obtained.
[0011] Compared with the prior art, the beneficial effects and advantages of the present invention are: 1. The present invention uses TiCoNbAl-based alloy, anti-wear agent, heat transfer agent, reinforcing agent and curing agent as raw materials, and obtains a multi-layered TiCoNbAl-based composite brake disc through process flows such as component design, layered batching, layer-by-layer preparation, spark plasma sintering and curing heat treatment. The multi-layered composite brake disc optimizes the material ratio, improves the material utilization rate, reduces the production cost, and is suitable for large-scale, mechanized and batch production; 2. The present invention distributes a large amount of heat transfer agent in the heat conductive layer and assists with a certain amount of reinforcing agent, so that it has good heat conduction ability and can effectively conduct the heat on the surface of the friction layer to the base layer. This significantly reduces the high temperature of the friction surface while ensuring that the friction surface has high hardness and excellent friction and wear performance.
[0012] 3. The Co element in the TiCoNbAl-based alloy of the present invention is a high-temperature resistant material, which can enable the brake disc to obtain a good braking effect in a high-temperature environment, and the Co element can significantly improve the hardness, rigidity and wear resistance of the material.
[0013] 4. The multi-layer TiCoNbAl-based composite brake disc designed by the present invention significantly improves the compressive resistance, compatibility, bonding and mechanical properties of each layer structure, and the multi-layer composite brake disc can be controlled and prepared, with a simple preparation method, high preparation efficiency and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The present invention is a flow chart of the preparation process adopted by the present invention.
[0015] Figure 2 The friction coefficient curve of the multi-layer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown.
[0016] Figure 3 This is a bar graph showing the wear rate of the multi-layer TiCoNbAl-based composite brake discs prepared in Examples 1-3.
[0017] Figure 4 This is an electron microscope morphology image of the bonding state between the heat conductive layer and the base layer of the multi-layer TiCoNbAl-based composite material brake disc prepared in Example 2.
[0018] Figure 5 This is an electron probe image of the friction and wear surface of the multilayer TiCoNbAl-based composite brake disc prepared in Example 2.
[0019] Figure 6 This is a field emission scanning electron microscope image of the friction and wear surface of the multilayer TiCoNbAl-based composite material brake disc prepared in Example 3.
[0020] Figure 7 This is a 3D microscopic morphology of the friction and wear of the multilayer TiCoNbAl-based composite material brake disc prepared in Example 3. DETAILED DESCRIPTION
[0021] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example
[0022] A multi-layer TiCoNbAl-based composite brake disc is made of TiCoNbAl-based alloy, anti-wear agent, heat conductive agent, reinforcing agent and curing agent as raw materials. The structure is divided into three-layer composite structure, and the thickness of each layer is calculated by volume percentage (thickness): friction layer 12%, heat conductive layer 25% and base layer 63%.
[0023] like Figure 1 As shown, the preparation process of the multilayer TiCoNbAl-based composite brake disc includes the following steps: 1) Preparation of raw materials for each layer structure: the mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the friction layer are 8wt.%TiCoNbAl-based alloy, 39wt.% anti-wear agent, 10wt.% thermal conductivity agent, 13wt.% reinforcing agent and 30wt.% curing agent, respectively, wherein the composition ratio of TiCoNbAl-based alloy is 67at.%Ti-12at.%Co-9at.%Nb-8at.%Al-2.9at.%B-0.5at.%Tb-0.3at.%Ce-0.3at.%Yb; anti-wear agent It is composed of 30wt.% cerium lanthanum rare earth phosphate, 30wt.% cubic boron nitride, 20wt.% calcium fluoride and 20wt.% barium fluoride; the thermal conductivity agent is composed of 30wt.% graphene, 30wt.% silicene and 40wt.% tungsten disulfide; the reinforcing agent is composed of 35wt.% basic magnesium sulfate whiskers, 25wt.% potassium titanate whiskers and 40wt.% calcium carbonate whiskers; the curing agent is composed of 50wt.% aluminum-based alloy, 15wt.% econazole ointment and 35wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is 45at.% Al-35at.% Ag-20at.% Sn. The mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the thermal conductive layer are 28wt.%TiCoNbAl-based alloy, 12wt.% anti-wear agent, 10wt.% thermal conductivity agent, 45wt.% reinforcing agent and 5wt.% curing agent, respectively. The composition ratio of TiCoNbAl-based alloy is 67at.%Ti-12at.%Co-9at.%Nb-8at.%Al-2.9at.%B-0.5at.%Tb-0.3at.%Ce-0.3at.%Yb; the anti-wear agent is 25wt.% It is composed of cerium lanthanum rare earth phosphate, 35wt.% cubic boron nitride, 20wt.% calcium fluoride and 20wt.% barium fluoride; the thermal conductivity agent is composed of 25wt.% graphene, 30wt.% silicene and 45wt.% tungsten disulfide; the reinforcing agent is composed of 35wt.% basic magnesium sulfate whisker, 25wt.% potassium titanate whisker and 40wt.% calcium carbonate whisker; the curing agent is composed of 25wt.% aluminum-based alloy, 25wt.% econazole ointment and 50wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is 45at.% Al-40at.% Ag-15at.% Sn. The matrix layer is 100wt.% TiCoNbAl-based alloy, and the composition ratio of the TiCoNbAl-based alloy is 67at.%Ti-12at.%Co-9at.%Nb-8at.%Al-2.9at.%B-0.5at.%Tb-0.3at.%Ce-0.3at.%Yb.
[0024] 2) The powders of each layer of materials obtained in step 1) are subjected to mechanical vibration mixing treatment, wherein the mechanical vibration frequency is 65 Hz, the vibration force is 9000 N, and the oscillation time is 80 min.
[0025] 3) The uniformly mixed powders of each layer obtained in step 2) are subjected to hot pressing and sintering, wherein the hot pressing pressure is 10 MPa, the pressing temperature is 100°C, the heat preservation and pressure holding time is 150 min, and the air is released for 5 seconds every 20 seconds, and the operation is repeated 6 times.
[0026] 4) The three-layer pressed sheet obtained in step 3) is loaded into a graphite mold with a diameter of 45 mm in the order of friction layer, thermal conductive layer and substrate layer for spark plasma sintering, wherein the sintering temperature is 1000°C, the sintering heating rate is 90°C / min, the sintering pressure is 22 MPa, the sintering holding time is 125 min, the sintering protective gas is argon, and the argon gas introduction rate is 70 mL / min.
[0027] 5) The brake disc obtained in step 4) is subjected to a curing heat treatment process to improve the bonding performance of each layer of powder, wherein the curing heat treatment is first heated to 120°C in a vacuum drying oven for 2.5 hours, then heated to 175°C for 6.5 hours, then heated to 220°C for 3.2 hours, and finally gradually cooled to room temperature.
[0028] 6) The brake disc obtained in step 5) is subsequently machined, and the brake disc is respectively subjected to disc grinding using grinding equipment according to technical requirements, with a grinding speed of 425 r / min; the burrs and flashes around the polishing machine are cleaned, and the electrostatic spraying process equipment speed is 800 r / min, the temperature is 55°C, etc., to finally obtain a multilayer TiCoNbAl-based composite brake disc.
[0029] Figure 2 The friction coefficient curve of the multi-layer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown. Figure 3 The wear rate bar graph of the multilayer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown in FIG. Figure 2 and Figure 3 As shown in the figure, the friction coefficient of the multilayer TiCoNbAl-based composite brake disc prepared in Example 1 is moderate, about 1.03, and the wear rate is low, about 3.35×10 -6 cm 3 ·N -1 ·m -1 This indicates that the multilayer TiCoNbAl-based composite brake disc prepared in Example 1 has excellent friction reduction and anti-wear properties. Example
[0030] A multi-layer TiCoNbAl-based composite brake disc is made of TiCoNbAl-based alloy, anti-wear agent, heat conductive agent, reinforcing agent and curing agent as raw materials. The structure is divided into three-layer composite structure. The thickness of each layer is calculated by volume percentage (thickness): friction layer is 18%, heat conductive layer is 37% and base layer is 45%.
[0031] like Figure 1 As shown, the preparation process of the multilayer TiCoNbAl-based composite brake disc includes the following steps: 1) Preparation of raw materials for each layer structure: the mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the friction layer are 10wt.%TiCoNbAl-based alloy, 30wt.% anti-wear agent, 18wt.% thermal conductivity agent, 25wt.% reinforcing agent and 17wt.% curing agent, respectively. The composition ratio of TiCoNbAl-based alloy is 55at.%Ti-14at.%Co-13at.%Nb-12at.%Al-4at.%B-0.9at.%Tb-0.6at.%Ce-0.5at.%Yb; anti-wear agent It is composed of 33wt.% cerium lanthanum rare earth phosphate, 27wt.% cubic boron nitride, 20wt.% calcium fluoride and 20wt.% barium fluoride; the thermal conductivity agent is composed of 50wt.% graphene, 25wt.% silicene and 25wt.% tungsten disulfide; the reinforcing agent is composed of 50wt.% basic magnesium sulfate whisker, 20wt.% potassium titanate whisker and 30wt.% calcium carbonate whisker; the curing agent is composed of 65wt.% aluminum-based alloy, 10wt.% econazole ointment and 25wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is 60at.% Al-20at.% Ag-20at.% Sn. The mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the thermal conductive layer are 32wt.%TiCoNbAl-based alloy, 17wt.% anti-wear agent, 17wt.% thermal conductivity agent, 25wt.% reinforcing agent and 9wt.% curing agent, respectively. The composition ratio of TiCoNbAl-based alloy is 55at.%Ti-14at.%Co-13at.%Nb-12at.%Al-4at.%B-0.9at.%Tb-0.6at.%Ce-0.5at.%Yb; the anti-wear agent is 25wt.%Ti. .% cerium lanthanum rare earth phosphate, 35wt.% cubic boron nitride, 25wt.% calcium fluoride and 15wt.% barium fluoride; the thermal conductivity agent is composed of 45wt.% graphene, 20wt.% silicene and 35wt.% tungsten disulfide; the reinforcing agent is composed of 45wt.% basic magnesium sulfate whisker, 25wt.% potassium titanate whisker and 30wt.% calcium carbonate whisker; the curing agent is composed of 45wt.% aluminum-based alloy, 15wt.% econazole ointment and 40wt.% dicyandiamide, wherein the aluminum-based alloy component ratio is 45at.% Al-40at.% Ag-15at.% Sn. The matrix layer is 100wt.% TiCoNbAl-based alloy, and the composition of the TiCoNbAl-based alloy is 55at.%Ti-14at.%Co-13at.%Nb-12at.%Al-4at.%B-0.9at.%Tb-0.6at.%Ce-0.5at.%Yb.
[0032] 2) The material powders of each layer obtained in step 1) are subjected to mechanical vibration mixing treatment, wherein the mechanical vibration frequency is 95 Hz, the vibration force is 11000 N, and the oscillation time is 90 min.
[0033] 3) The uniformly mixed powders of each layer obtained in step 2) are subjected to hot pressing and sintering, wherein the hot pressing pressure is 12 MPa, the pressing temperature is 135°C, the heat preservation and pressure holding time is 165 min, and the air is released for 6 seconds every 25 seconds, and the operation is repeated 8 times.
[0034] 4) The three-layer pressed sheet obtained in step 3) is loaded into a graphite mold with a diameter of 55 mm in the order of friction layer, thermal conductive layer and substrate layer for spark plasma sintering, wherein the sintering temperature is 1100°C, the sintering heating rate is 100°C / min, the sintering pressure is 25MPa, the sintering holding time is 145min, the sintering protective gas is argon, and the argon gas introduction amount is 105mL / min.
[0035] 5) The brake disc obtained in step 4) is subjected to a curing heat treatment process to improve the bonding performance of each layer of powder, wherein the curing heat treatment is to first heat the temperature to 145°C in a vacuum drying oven for 3.5 hours, then heat the temperature to 185°C for 7.5 hours, then heat the temperature to 250°C for 3.6 hours, and finally gradually cool to room temperature.
[0036] 6) The brake disc obtained in step 5) is subsequently machined, and the brake disc is respectively subjected to disc grinding using grinding equipment according to technical requirements, with a grinding speed of 475 r / min; the burrs and flashes around the polishing machine are cleaned, and the electrostatic spraying process equipment speed is 920 r / min, the temperature is 65°C, etc., to finally obtain a multilayer TiCoNbAl-based composite brake disc.
[0037] Figure 4 This is an electron microscope morphology image of the bonding state between the heat conductive layer and the base layer of the multi-layer TiCoNbAl-based composite material brake disc prepared in Example 2. Figure 5 This is an electron probe image of the friction and wear surface of the multilayer TiCoNbAl-based composite brake disc prepared in Example 2. Figure 2 The friction coefficient curve of the multi-layer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown. Figure 3 The wear rate bar graph of the multilayer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown in FIG. Figure 2 and Figure 3 As shown in the figure, the friction coefficient of the multilayer TiCoNbAl-based composite brake disc prepared in Example 2 is moderate, with a value of about 0.81, and the wear rate is low, with a value of about 2.97×10 -6 cm 3 ·N -1·m -1 This indicates that the multilayer TiCoNbAl-based composite brake disc prepared in Example 2 has excellent friction reduction and anti-wear properties. Example
[0038] A multi-layer TiCoNbAl-based composite brake disc is made of TiCoNbAl-based alloy, anti-wear agent, heat conductive agent, reinforcing agent and curing agent as raw materials. The structure is divided into three-layer composite structure. The thickness of each layer is calculated by volume percentage (thickness): friction layer 15%, heat conductive layer 31% and base layer 54%.
[0039] like Figure 1 As shown, the preparation process of the multilayer TiCoNbAl-based composite brake disc includes the following steps: 1) Preparation of raw materials for each layer structure: the mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the friction layer are 9wt.% TiCoNbAl-based alloy, 35wt.% anti-wear agent, 14wt.% thermal conductivity agent, 18wt.% reinforcing agent and 24wt.% curing agent, respectively. The composition ratio of TiCoNbAl-based alloy is 60at.%Ti-14.5at.%Co-11at.%Nb-10at.%Al-3at.%B-0.7at.%Tb-0.5at.%Ce-0.3at.%Yb; the anti-wear agent is composed of 32wt.% phosphorus cerium lanthanum rare earth, 28wt.% cubic boron nitride, 25wt.% t.% calcium fluoride and 15wt.% barium fluoride; the thermal conductivity agent is composed of 40wt.% graphene, 25wt.% silicene and 35wt.% tungsten disulfide; the reinforcing agent is composed of 40wt.% basic magnesium sulfate whisker, 30wt.% potassium titanate whisker and 30wt.% calcium carbonate whisker; the curing agent is composed of 60wt.% aluminum-based alloy, 15wt.% econazole ointment and 25wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is 50at.% Al-30at.% Ag-20at.% Sn. The mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent in the thermal conductive layer are 30wt.% TiCoNbAl-based alloy, 15wt.% anti-wear agent, 14wt.% thermal conductivity agent, 34wt.% reinforcing agent and 7wt.% curing agent, respectively. The composition ratio of TiCoNbAl-based alloy is 60at.% Ti-14.5at.% Co-11at.% Nb-10at.% Al-3at.% B-0.7at.% Tb-0.5at.% Ce-0.3at.% Yb; the anti-wear agent is 25wt.% Ti. .% cerium lanthanum rare earth phosphate, 40wt.% cubic boron nitride, 20wt.% calcium fluoride and 15wt.% barium fluoride; the thermal conductivity agent is composed of 35wt.% graphene, 30wt.% silicene and 35wt.% tungsten disulfide; the reinforcing agent is composed of 40wt.% basic magnesium sulfate whisker, 35wt.% potassium titanate whisker and 25wt.% calcium carbonate whisker; the curing agent is composed of 35wt.% aluminum-based alloy, 20wt.% econazole ointment and 45wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is 37at.% Al-38at.% Ag-25at.% Sn. The matrix layer is 100wt.% TiCoNbAl-based alloy, and the TiCoNbAl-based alloy composition is 60at.% Ti-14.5at.% Co-11at.% Nb-10at.% Al-3at.% B-0.7at.% Tb-0.5at.% Ce-0.3at.% Yb.
[0040] 2) The powders of each layer of materials obtained in step 1) are subjected to mechanical vibration mixing treatment, wherein the mechanical vibration frequency is 85 Hz, the vibration force is 10000 N, and the oscillation time is 85 min.
[0041] 3) The uniformly mixed powders of each layer obtained in step 2) are hot pressed and sintered, wherein the pressure applied in the hot pressing is 11 MPa, the pressing temperature is 125°C, the heat preservation and pressure holding time is 155 min, and the air is released for 5 seconds every 22 seconds, and the operation is repeated 7 times.
[0042] 4) The three-layer pressed sheet obtained in step 3) is sequentially loaded into a graphite mold with a diameter of 52 mm in the order of friction layer, heat conductive layer and substrate layer for spark plasma sintering, wherein the sintering temperature is 1050°C and the sintering heating rate is 110 o C / min, the sintering pressure is 23MPa, the sintering holding time is 135min, the sintering protective gas is argon, and the argon flow rate is 95mL / min.
[0043] 5) The brake disc obtained in step 4) is subjected to a curing heat treatment process to improve the bonding performance of each layer of powder, wherein the curing heat treatment is to first heat the temperature to 135°C in a vacuum drying oven for 3.2 hours, then heat the temperature to 182°C for 7.1 hours, then heat the temperature to 230°C for 3.4 hours, and finally gradually cool to room temperature.
[0044] 6) The brake disc obtained in step 5) is subsequently machined, and the brake disc is respectively subjected to disc grinding using grinding equipment according to technical requirements, with a grinding speed of 458 r / min; the burrs and flashes around the polishing machine are cleaned, and the electrostatic spraying process equipment speed is 875 r / min, the temperature is 60°C, etc., to finally obtain a multilayer TiCoNbAl-based composite brake disc.
[0045] Figure 6 This is a field emission scanning electron microscope image of the friction and wear surface of the multilayer TiCoNbAl-based composite material brake disc prepared in Example 3. Figure 7 This is a 3D microscopic morphology of the friction and wear of the multilayer TiCoNbAl-based composite material brake disc prepared in Example 3. Figure 2 The friction coefficient curve of the multi-layer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown. Figure 3 The wear rate bar graph of the multilayer TiCoNbAl-based composite brake disc prepared in Examples 1-3 is shown in FIG. Figure 2 and Figure 3 As shown in the figure, the friction coefficient of the multilayer TiCoNbAl-based composite brake disc prepared in Example 3 is moderate, with a value of about 0.72, and the wear rate is low, with a value of about 3.85×10 -6 cm 3 ·N-1 ·m -1 This indicates that the multilayer TiCoNbAl-based composite brake disc prepared in Example 3 has excellent friction reduction and anti-wear properties.
[0046] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A multi-layer TiCoNbAl-based composite brake disc, characterized in that: The multi-layered TiCoNbAl-based composite brake disc is composed of a friction layer, a heat-conducting layer and a base layer laminated in sequence, wherein the layer thickness ratio of the friction layer, the heat-conducting layer and the base layer is (12-18):(25-38):(45-65); the mass fractions of the TiCoNbAl-based alloy, the anti-wear agent, the heat-conducting agent, the reinforcing agent and the curing agent in the friction layer are (8-10) wt.%, (30-40) wt.%, (10-12) wt.%, (13-25) wt.% and (15-35) wt.% respectively; the TiCoNbAl-based alloy, the heat-conducting agent, the heat-conducting agent, the reinforcing agent and the curing agent in the heat-conducting ... heat-conducting agent and the curing agent in the friction layer are (8-10) wt.%, (30-40) wt.%, (10-12) wt.%, (13-25) wt.% and (15-35) wt.% respectively; the TiCoNbAl-based alloy, the heat-conducting agent, the heat-conducting agent The mass fractions of TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent are (25-35)wt.%, (12-18)wt.%, (10-18)wt.%, (30-45)wt.% and (5-10)wt.% respectively; the matrix layer is 100wt.% TiCoNbAl-based alloy; the friction coefficient of the multilayer TiCoNbAl-based composite brake disc is moderate and has a small fluctuation range. The friction coefficient is 0.72-1.03 and the wear rate is (2.97-3.85)×10 -6 cm 3 ·N -1 ·m -1 .
2. The multi-layered TiCoNbAl-based composite brake disc according to claim 1, characterized in that: The anti-wear agent in the friction layer is composed of (30-35) wt.% cerium lanthanum rare earth phosphorus, (25-30) wt.% cubic boron nitride, (20-25) wt.% calcium fluoride and (15-20) wt.% barium fluoride; the heat transfer agent is composed of (30-50) wt.% graphene, (20-30) wt.% silicene and (25-40) wt.% tungsten disulfide; the reinforcing agent is composed of (35-50) wt.% basic sulfuric acid The invention is composed of magnesium whiskers, (20-35) wt.% potassium titanate whiskers and (25-40) wt.% calcium carbonate whiskers; the curing agent is composed of (50-65) wt.% aluminum-based alloy, (10-20) wt.% econazole ointment and (20-35) wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is (45-60) at.% Al-(20-35) at.% Ag-(10-25) at.% Sn.
3. The multi-layered TiCoNbAl-based composite brake disc according to claim 1, characterized in that: The anti-wear agent in the heat-conducting layer is composed of (20-30) wt.% cerium lanthanum rare earth phosphorus, (30-45) wt.% cubic boron nitride, (20-25) wt.% calcium fluoride and (15-20) wt.% barium fluoride; the heat-conducting agent is composed of (25-45) wt.% graphene, (20-40) wt.% silicene and (30-45) wt.% tungsten disulfide; the reinforcing agent is composed of (35-45) wt.% basic sulfuric acid The invention is composed of magnesium whiskers, (20-45) wt.% potassium titanate whiskers and (20-40) wt.% calcium carbonate whiskers; the curing agent is composed of (20-45) wt.% aluminum-based alloy, (15-25) wt.% econazole ointment and (40-60) wt.% dicyandiamide, wherein the composition ratio of the aluminum-based alloy is (30-45) at.% Al-(35-50) at.% Ag-(15-30) at.% Sn.
4. The multi-layered TiCoNbAl-based composite material brake disc according to claim 1, characterized in that: The composition ratio of the TiCoNbAl-based alloy in the friction layer, the heat-conducting layer and the base layer is (55-67) at.% Ti-(12-14.5) at.% Co-(9-13) at.% Nb-(8-12) at.% Al-(2.9-4) at.% B-(0.5-0.9) at.% Tb-(0.3-0.6) at.% Ce-(0.3-0.5) at.% Yb.
5. A method for preparing a multilayer TiCoNbAl-based composite brake disc according to claim 1, characterized in that The specific preparation process is: using TiCoNbAl-based alloy, anti-wear agent, thermal conductivity agent, reinforcing agent and curing agent as raw materials, the multi-layer TiCoNbAl-based composite brake disc is obtained after the material design, calculation, preparation, vibration mixing, hot pressing, spark plasma sintering, curing heat treatment and subsequent machining of each layer.
6. The method for preparing a multilayer TiCoNbAl-based composite brake disc according to claim 5, characterized in that The specific preparation steps are: 1) Weigh the raw materials according to the various components of the friction layer, heat conductive layer and matrix layer in the multilayer TiCoNbAl-based composite material; 2) The powders of each layer of materials obtained in step 1) are subjected to mechanical vibration mixing treatment, wherein the mechanical vibration frequency is 65-95 Hz, the vibration force is 9000-11000 N, and the vibration time is 80-90 min; 3) hot pressing and sintering the uniformly mixed powders of each layer obtained in step 2), wherein the pressure applied in the hot pressing is 10-12 MPa, the pressing temperature is 100-135°C, the heat preservation and pressure holding time is 150-165 min, the air is released for 5-6 seconds every 20-25 seconds, and the operation is repeated 6-8 times; 4) The three-layer pressed sheet obtained in step 3) is sequentially loaded into a graphite mold according to the order of the friction layer, the heat conductive layer and the substrate layer for spark plasma sintering, wherein the sintering temperature is 1000-1100° C., the sintering heating rate is 90-110° C. / min, the sintering pressure is 22-25 MPa, the sintering holding time is 125-145 min, the sintering protective gas is argon, and the argon gas introduction rate is 70-105 mL / min; 5) subjecting the brake disc obtained in step 4) to a curing heat treatment process to improve the bonding performance of each layer of powder, wherein the curing heat treatment is first heated to 120-145°C in a vacuum drying oven for 2.5-3.5 hours, then heated to 175-185°C for 6.5-7.5 hours, then heated to 220-250°C for 3.2-3.6 hours, and finally gradually cooled to room temperature; 6) The brake disc obtained in step 5) is subsequently machined, and the brake disc is respectively subjected to disc grinding by a grinding device according to technical requirements, and the burrs and flashes around the brake disc are cleaned by a polishing machine and electrostatic spraying is performed, and finally a multilayer TiCoNbAl-based composite brake disc is obtained.
Citation Information
Patent Citations
A composite material brake disc, its preparation method and application
CN107100949B
A composite material brake disc
CN112413012B
Cited By
Lightweight carbon ceramic-aluminum composite brake disc and preparation method thereof
CN120885690A